2012
DOI: 10.1590/s0004-282x2012000400004
|View full text |Cite
|
Sign up to set email alerts
|

HAM/TSP: association between white matter lesions on magnetic resonance imaging, clinical and cerebrospinal fluid findings

Abstract: OBJECTIVE: To investigate the association between clinical data, white matter lesions and inflammatory cerebrospinal fluid (CSF) findings in HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP). METHOD: We studied brain and cervical spinal cord on magnetic resonance imaging (MRI) and CSF examinations of 28 Brazilian HAM/TSP patients. RESULTS: The majority of patients had severe neurological incapacity with EDSS median of 6.5 (3-8). The brain MRI showed white matter lesions (75%) and atrophy (14%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Among our HAM/TSP patients, most showed small lesions in the subcortical and periventricular WM, however these lesions were not associated with symptoms, as reported 45 , 46 . MRI findings of 28 Brazilian HAM/TSP patients, mostly with severe neurological incapacity, showed hyper intense lesions in brain WM, indirect atrophy signs and occasionally spinal cord lesions 44 . Among our HAM/TSP patients, no sign of spinal cord swelling was reported, whereas only one patient showed spinal cord atrophy, however variable levels of spinal cord abnormalities have been reported 46 , 47 .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Among our HAM/TSP patients, most showed small lesions in the subcortical and periventricular WM, however these lesions were not associated with symptoms, as reported 45 , 46 . MRI findings of 28 Brazilian HAM/TSP patients, mostly with severe neurological incapacity, showed hyper intense lesions in brain WM, indirect atrophy signs and occasionally spinal cord lesions 44 . Among our HAM/TSP patients, no sign of spinal cord swelling was reported, whereas only one patient showed spinal cord atrophy, however variable levels of spinal cord abnormalities have been reported 46 , 47 .…”
Section: Discussionmentioning
confidence: 63%
“…Unspecific periventricular and subcortical white matter (WM) lesions on brain MRI are frequent in HAM/TSP patients 41 . It has been suggested that WM lesions may represent small vessel vasculitis and since they predominate in middle aged/older patients, they could be due to degenerative microangiopathy 43 , 44 . Among our HAM/TSP patients, most showed small lesions in the subcortical and periventricular WM, however these lesions were not associated with symptoms, as reported 45 , 46 .…”
Section: Discussionmentioning
confidence: 76%
“…22 Human T-cell lymphotropic virus 1 neurologic complex has been described as an iceberg model, with human T lymphotropic-associated myelopathy and/or tropical spastic paraparesis forming its tip, which develops in 2%-4% of the infected population. 23,24 The diagnosis is confirmed by detecting antihuman T-cell lymphotropic virus 1 antibodies in CSF and serum. Although the exact mechanism of CNS disease is unknown, it has been postulated to be due to direct viral invasion and/or autoimmune mechanisms that result in brain and spinal cord infiltration by lymphocytes and monocytes that involve the gray and white matter.…”
Section: Human T-cell Lymphotropic Virusmentioning
confidence: 94%
“…Eradication of HTLV might be possible by elimination of infected monocytes and through allogeneic hematopoietic stem cell transplantation [18]. CNS imaging has advanced so that asymptomatic carriers may be distinguished from patients with early HAM/TSP [19]. New imaging techniques were presented which could potentially be used to also measure and monitor treatment response.…”
Section: Introductionmentioning
confidence: 99%